American Ways: A Guide for Foreigners in the United States and The 10 Lenses: Your Guide to Living and Working in a Multicultural World - Pat Melgares (Journal of Applied Communications, 2006)
Two book reviews: American Ways: A Guide for Foreigners in the United States, by Gary Althen with Amanda R. Doran and Susan J. Szmania; and The 10 Lenses: Your Guide to Living and Working in a Multicultural World, by Mark A. Williams.